Protective Effects of Baobab Plant Extract on Doxorubicin-induced Histological and Biological Changes on Liver and Kidney of Albino Rats - Alyaa Al-Safo; Saif Yahya; Abeer Abdel Rasool (Al-Anbar Medical Journal)
Background: Doxorubicin (DOX), a chemotherapeutic drug, is effective against various cancers but can cause liver and kidney damage due to oxidative stress and inflammation.Objectives: To determine whether managing albino rats with an aqueous extract of the baobab plant can reduce the potential histological effects of DOX on the renal and hepatic tissues.Materials And Methods: Forty rats were acclimatized under controlled conditions and divided into four groups: Control group receiving saline, DOX group receiving one intraperitoneal injection of 15 mg/kg DOX, DOX + baobab group co-administered with DOX at 15 mg/kg intraperitoneally plus baobab extract (500 mg/kg/day) orally, and the baobab-only group administered with 500 mg/kg/day baobab extract. Then, the baobab effects on liver and kidney function after the use of DOX were evaluated.Results: Rats treated with DOX had higher serum urea and creatinine levels. While baobab extract, when co-administered with DOX, reduced urea and creatinine levels, thus bringing them closer to the control group and pointing towards the protective potential of baobab against DOX-induced nephrotoxicity. The effect of DOX treatment was an increase in the levels of the liver markers (alanine aminotransferase and aspartate aminotransferase), whereas baobab resulted in significant decreases in these liver markers. After receiving DOX, the baobab extract exists in advanced hepatic and renal function in association with the control group. Baobab had significant possessions on kidney function and may be experienced  incompatible tissue damage spread by DOX.Conclusion: Co-administration of baobab extract with DOX improved kidney and liver function.